2011
DOI: 10.1007/s10706-011-9465-2
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element and Reliability Analyses for Slope Stability of Subansiri Lower Hydroelectric Project: A Case Study

Abstract: The partly constructed and excavated power house slopes of Subansiri Lower Hydroelectric Project experienced extensive collapses through complex mode of failure. A detailed study is attempted in this paper to understand the reasons for the failure and assess the stability of the existing constructed slopes using limit equilibrium and FEM solutions and also to propose modified design for rebuilding the slopes. To take into account the uncertainty associated with the rockmass and soil properties, probability and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 20 publications
(21 reference statements)
1
5
0
Order By: Relevance
“…Typically, numerical simulations are used to study such complexity, making it possible to take into account all governing factors. Numerous instances of the successful use of numerical tools to study the behavior of the slope have been documented (Pal et al 2012, Rathod andRao 2012). Three methods exist to perform 3D slope stability analyses: the Finite Element Method, the Limit Analysis Method, and the Limit Equilibrium Method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, numerical simulations are used to study such complexity, making it possible to take into account all governing factors. Numerous instances of the successful use of numerical tools to study the behavior of the slope have been documented (Pal et al 2012, Rathod andRao 2012). Three methods exist to perform 3D slope stability analyses: the Finite Element Method, the Limit Analysis Method, and the Limit Equilibrium Method.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was discovered that the vulnerability increased significantly in wet conditions. Rathod and Rao (2012) gave a comprehensive numerical analysis of the slopes' failure in the lower Subanshiri hydroelectric generating project. For roadcutting slopes, Singh et al (2008) were observed doing comparable work in the Uttarakhand region.…”
Section: Introductionmentioning
confidence: 99%
“…Landslide characterisation is described through various means, e.g. landslide mechanisms and occurrence force (Leroueil 2001;Take et al 2004;Huang et al 2022), failure mode analysis/simulation (Liu et al 2015;Sidle and Bogaard 2016;Han et al 2019a), sensitivity/reliability analysis (Rathod and Rao 2012;Nguyen and Likitlersuang 2019;Huang et al 2020), and the design of effective countermeasure and their field optimisation (Popescu and Sasahara 2009;Han et al 2019b;Chen et al 2021). In addition to the physical science investigation, socio-economic analysis of the landslide issues helps to infer the vulnerability of the people living on dangerous slopes and effectively promotes the disaster risk governance (Antronico et al 2020;Vij et al 2020;Alam and Ray-Bennett 2021;Huang et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the time-dependent deformation characteristics of rock and soil, the deformation of slope is also affected by excavation disturbance, reservoir water and rainfall during construction. G. W. Rathod and K. S. Rao [3] discussed the stability of rock slope of India Subansiri Lower hydropower station based on limit equilibrium and finite element analysis. H. J.…”
Section: Introductionmentioning
confidence: 99%